The Impact of Language on Building the Internal Market: The Consumer Transactions Perspective - Filipowski, Oskar (University of Wroclaw. Faculty of Law, Administration & Economics, 2014)
By the introduction of Directive 2011/83/EU the European Union is trying to achieve full harmonization of consumer law in the Member States. It is hoped that this will boost cross-border online sales, which constitute a very low percentage of all consumer transactions at the moment. In this paper the author points out some language issues that may hinder the harmonization process, and tries to find and briefly characterize solutions that would prevent the negative effect of language divergence in EU Member States.
Keywords: dyrektywa 2011/83/UE; prawo konsumenckie; transgraniczna sprzedaż online